Reproductive Health Education: Efforts to Improve Women's Knowledge and Attitudes Toward Cervical Cancer Screening - Nathasia Haryono; Fiyola Ladyvia; Ismah Khaerunisa; Martine Meha; Kurniawati Kurniawati (JURNAL PENGMAS KESTRA (JPK), 2026)
The low coverage of early detection for cervical cancer in Deli Serdang Regency is driven by a lack of reproductive health literacy and high psychological barriers within the community. This Community Service (PKM) program aimed to enhance knowledge, improve attitudes, and stimulate actual behaviors among Women of Reproductive Age (WUS) toward VIA (Visual Inspection with Acetic Acid) and Pap Smear screenings. The implementation method utilized a structured health promotion approach comprising three systematic stages: preparation (coordination and licensing), implementation (interactive education and group counseling), and descriptive evaluation (pre-test, post-test, and action tracking). The target audience consisted of 40 women of reproductive age in Sadar Barat Village, Deli Serdang. The evaluation results demonstrated a significant increase in the cognitive domain, where the percentage of participants with good knowledge skyrocketed from 10% to 85%. This improvement in literacy simultaneously dismantled participants' emotional resistance, as evidenced by a shift to highly positive and supportive attitudes toward the screening program, reaching 90%. The most crucial impact was observed during the action tracking phase, where the facilitation of clinical access in collaboration with the village midwife successfully motivated 70% of the total participants to voluntarily undergo independent screenings (VIA/Pap Smear). In conclusion, this integrative and empathetic community service model has proven effective in dismantling community psychological barriers and is highly recommended as an applicable health promotion formula to boost national cervical cancer screening coverage sustainably from the primary community level.